The Implementation of Sort, Set in Order, Shine, Standardize, and Sustain as Occupational Accident Preventions at PT X - Bayu Adi Radityo (The Indonesian Journal of Occupational Safety and Health, 2019)
Introduction: The implementation of qualified sort, set in order, shine, standardize, and sustain (5S) is a significant factor to prevent the occurrence of occupational accidents in companies with a high-risk level of occupational accidents, such as being exposed to falling objects or tripped with objects, especially in departments that handle goods or materials. This research aims to identify the enactment of 5S as occupational accidents preventions in the logistic department at PT. X. Metods: This research is descriptive-analytic research which describes the company policy regarding the employment of 5S and the characteristics of the workers in the logistic department at PT. X. Moreover, this research also intends to analyze the strength of the relationship between the workers’ characteristics based on the correlation coefficient value by using the cross-sectional approach. The data is in the form of secondary data obtained by using questionnaires and interview. Results: It has been noticed that there is a qualified policy regarding the implementation of 5R in the form of technical instructions and the SOP of the company that has been well-enacted. Majority of the workers in the logistic department at PT. X is between 15-30 years old with high school educational attainment and has been serving in the company for <6 years. It is also perceived that all workers in the logistic department have a good 5S understanding level and good attitudes toward the implementation of 5R. However, there is a difference in the direction of the relationship of the variables analyzed; one is a negative relationship while the other is a positive relationship. Conclusion: It can be affirmed that PT. X has implemented 5S in a good way, seen from the understanding level of the workers regarding 5S or the attitude of the workers in implementing 5S, particularly in the logistic department. This is also proven by the company policy on the enactment of 5S that has been well-carried out. Keywords: 5S implementation, logistic, occupational accidents